Effects of the Rates on the Performance and Pressure Pulsations of a High-Speed Pump with Straight Blade - Hao Jia; Xianghui Su; Wei Jin (Shock and Vibration)
Along with the crucial requirement for efficiency improvement in the cutting-edge petrochemical technology, the evaluation of the dynamic performance characteristics of high-speed pump is becoming increasingly important. It has become a main topic in the research of high-speed pump to minimize the pressure pulsation induced by the fluid in the pump body, so as to reduce the mechanical vibration. Although the research on the transient flow characteristic and pressure fluctuation of a high-speed pump with straight blades is of great significance, it has been seldom explored. In this work, the flow instability of a 16 straight-blade high-speed centrifugal pump is studied numerically at a rotational speed of 8500 rpm and flow rate of 3 m3/h. Results show that with the influence of rotor-stator interaction, time-domain pressure signals at the tongue show double peak characteristic, whereas a single peak characteristic exists at the diffuser wall. The pressure fluctuation near the tongue is reduced to approximately half of that at the volute wall by the water ring effect accompanied with the high-pressure factor. At the tongue region, the amplitude of the blade passing frequency is reduced by the unsteady flow, whereas the harmonic wave was increased at 2–4 times of the blade passing frequency.